Ultrasonography Profile of Myxomatous Mitral Valve Disease on An 11-Year-Old Poodle - Wah, Toh Pei; Wijaya, Agus; Murtiningrum, Fitria Senja; Iman, Bintang Nurul; Noviana, Deni (Universitas Airlangga, 2024)
Myxomatous mitral valve disease (MMVD) is a prevalent inherited mitral valve condition. This study aimed to evaluate the clinical manifestation of the cardiac condition MMVD in Poodles. Using ultrasonography (USG), this study examined the characteristics, progression, diagnosis, and treatment of MMVD in an 11-year-old Poodle. This case study was conducted at the Veterinary Teaching Hospital, School of Veterinary Medicine and Biomedical Sciences, utilizing a Chison Ebit60 with an 8–12 MHz curvilinear probe. The dog was positioned in the right parasternal recumbency position, and the long axis (RPLA) and short axis (RPSA) views were obtained. In the evaluation and diagnosis, B-Mode, M-Mode, and Color Flow Doppler (CFD) modes of ultrasonography were performed. The dog presented with coughing, and the physical examination revealed a grade 3–4 murmur. Based on B-mode cardiac monitoring, sinus arrhythmia, mitral valve thickness, and prolapses indicate MMVD. Mitral regurgitation was indicated by a decrease in heart rate and an increase in the left ventricle internal dimension (LVIDd) on the M-mode. Meanwhile, CFD's representation of turbulent flow confirmed mitral regurgitation results. The rise in blood pressure confirmed the presence of hypertension. Class B2 MMVD in Poodles has consequently been diagnosed in this case.